Women's Wage Theft: Explaining Gender Differences in Violations of Wage and Hour Laws. (November 2016) - Petrescu-Prahova, Miruna; Spiller, Michael W.
In this study, the authors identify and analyze a distinct and understudied source of gender inequality: gender differences in violations of wage-related workplace laws. The authors find that women have significantly higher rates of minimum wage and overtime violations than men and also lose more of their earnings to wage theft than men. In the case of minimum wage violations, the authors also find that nativity and immigration status strongly mediate this gender difference. Multivariate analysis suggests that demand-side characteristics—occupation and measures of nonstandard work and informality—account for more of the gender difference in minimum wage violations than do worker characteristics.